KAJIAN KANDUNGAN DAN KARAKTERISIK PATI RESISTEN DARI BERBAGAI VARIETAS PISANG - Musita, Nanti (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2009)
Banana production in Indonesia at this time is about 50 % from total production in Asia.In addition. It also has the immeasurable banana types. Banana represents a potential source dietary fibre. Dietary fibre including resistant starch has a very good contribution in keeping health. Eleven banana types werenused in this experiment, they were banana of ambon, batu, janten, kapas, kepok manado, kepok kuning, muli, nangka, raja bulu, raja sereh, and tanduk. The results indicate that (1) The starch yield and resistant starch banana of ambon were 8,58 % and 29,37 %, batu were 0,87 % and 39,35 %, janten were 3,95 % and 26,17 %, kapas were 5,08 % and 26,55 %, kepok kuning were 22,01 % and 27,70 %, kepok manado were 12,24 % and 27,21 %, muli were 6,62 % and 26,42 %, nangka were 3,12 % and 26,28 %, raja bulu were 24,12 % and 30,66 %, raja sereh were 2,32 % and 25,63 %, and tanduk were 2,07 % and 29,60 %, (2) Water absorpsion and swelling power banana of ambon were 1,44 ml/g and 2,53 g/g), batu were 0,80 ml/g and 1,76 g/g, kepok kuning were 1,49 ml/g and 2,58 g/g, raja bulu were 0,89 ml/g and 2,11 g/g, and tanduk were 1,32 ml/g and 2,23 g/g. It was also observed that the resistant starch was type 2 resistant starch. Keywords: Resistant starch, banana, swelling power